Inflation-linked bonds from a Central Bank perspective - Juan Angel Garcia; Adrian van Rixtel (European Central Bank (ECB), 2007)
Inflation-linked bond markets have experienced significant growth in recent years. This growth is somewhat surprising, for inflation-linked bonds cannot be considered a financial innovation and their development has taken place in a period of historically low global inflation and inflation expectations. In this context, the purpose of this paper is twofold. First, it provides a selective survey of the key arguments for and against the issuance of inflation-linked debt, and some of the factors that help to understand their recent growth. Second, it illustrates the use of these instruments to better monitor investors' inflation expectations and growth prospects from a central bank perspective.
Keywords: 330; Indexanleihe; Indexbindung; Inflation; Welt